An automated optimization strategy to design collimator geometry for small field radiation therapy systems. (6th April 2021) - Wang, Jinghui; Wang, Lei; Maxim, Peter G; Loo, Billy W
Abstract: Purpose . To develop an automated optimization strategy to facilitate collimator design for small-field radiotherapy systems. Methods and Materials. We developed an objective function that links the dose profile characteristics (FWHM, penumbra, and central dose rate) and the treatment head geometric parameters (collimator thickness/radii, source-to-distal-collimator distance (SDC)) for small-field radiotherapy systems. We performed optimization using a downhill simplex algorithm. We applied this optimization strategy to a linac-based radiosurgery system to determine the optimal geometry of four pencil-beam collimators to produce 5, 10, 15, and 20 mm diameter photon beams (from a 6.7 MeV, 2.1 mm FWHM electron beam). Two different optimizations were performed to prioritize minimum penumbra or maximum central dose rate for each beam size. We compared the optimized geometric parameters and dose distributions to an existing clinical system (CyberKnife). Results. When minimum penumbra was prioritized, using the same collimator thickness and SDC (40 cm) as a CyberKnife system, the optimized collimator upstream and downstream radii agreed with the CyberKnife system within 3%–14%, the optimized output factors agreed within 0%–8%, and the optimized transverse and percentage depth dose profiles matched those of the CyberKnife with the penumbras agreeing within 2%. However, when maximum dose rate was prioritized, allowing both the collimator thickness and SDC to change, the central dose rate for larger collimator sizes (10, 15, 20 mm) could be increased by about 1.5–2 times at the cost of 1.5–2 times larger penumbras. No further improvement in central dose rate for the 5 mm beam size could be achieved. Conclusions. We developed an automated optimization strategy to design the collimator geometry for small-field radiation therapy systems. Using this strategy, the penumbra-prioritized dose distribution and geometric parameters agree well with the CyberKnife system as an example, suggesting that this system was designed to prioritize sharp penumbra. This represents proof-of-principle that an automated optimization strategy may apply to more complex collimator designs with multiple optimization parameters.